1999
DOI: 10.1097/00005373-199903000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Head Trauma with Cervical Spine Injury, Spinal Cord Injury, or Both

Abstract: Approximately one third of patients with cervical spine and/or spinal cord injuries had moderate or severe head injuries. Brain damage was more frequently associated with upper cervical injury. Those patients with upper cervical injury are at greater risk of suffering from skull base fractures and severe intracranial hematomas than those with mid to lower cervical injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 10 publications
0
44
0
Order By: Relevance
“…37 Iida et al reported moderate or severe head injury in 35% of 188 patients with cervical spine or SCI. 29 In a study of spinal injuries at all levels limited to the pediatric age group, Cirak et al recorded a 37.4% prevalence of TBI. 9 In the current study, coincident TBI and GCS motor ≤ 4 are noted in 38.8% and 16.0% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…37 Iida et al reported moderate or severe head injury in 35% of 188 patients with cervical spine or SCI. 29 In a study of spinal injuries at all levels limited to the pediatric age group, Cirak et al recorded a 37.4% prevalence of TBI. 9 In the current study, coincident TBI and GCS motor ≤ 4 are noted in 38.8% and 16.0% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…'Primary' cervical spine injury may be associated with head injury in 24-35% of cases [10,[16][17][18][19][20], and among polytrauma victims requiring cervical spine stabilization surgery, only 74% suffered an isolated injury [21]. The prognosis in patients suffering both head and cervical injury is typically poor, with approximately 25% being discharged to a dedicated nursing facility with little prospect of recovery [22].…”
Section: Discussionmentioning
confidence: 99%
“…• Increased intracranial pressure [42][43][44][45] worsens the outcome of a population with co-existing head injury in up to one-third of cases [19].…”
mentioning
confidence: 99%
“…Scattered studies of CSI in clinical series composed of all trauma patients report CSI prevalences ranging from 1 to 14%. 59,87 However, unevaluable patients require a higher index of suspicion than the general trauma population, 5,46,51,64,80,96 with one patient series estimating that a GCS score ≤ 8 incurs an almost 6-fold increase in the risk of CSI.…”
mentioning
confidence: 99%